Contingent contracts in banking: Insurance or risk magnification? - Hans Gersbach (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
We examine whether the economy can be insured against banking crises with deposit and loan contracts contingent on macroeconomic shocks. We study banking competition and show that the private sector insures the banking system through such contracts, and banking crises are avoided, provided that failed banks are not bailed out. When risks are large, banks may shift part of them to depositors. In contrast, when banks are bailed out by the next generation, depositors receive non-contingent contracts with high interest rates, while entrepreneurs obtain loan contracts that demand high repayment in good times and low repayment in bad times. As a result, the present generation overinvests, and banks generate large macroeconomic risks for future generations, even if the underlying productivity risk is small or zero. We conclude that a joint policy package of orderly default procedures and contingent contracts is a promising way to reduce the threat of a fragile banking system.
urn:nbn:de:hebis:30:3-480039
Keywords: D41; E4; G2; 330; financial intermediation; macroeconomic risks; state-contingent contracts; banking regulation